Senam Hipertensi sebagai Alternatif Pencegahan dan Pengendalian Potensi Stroke di Lembaga Pemasyarakatan Kota Ambon - Rivai Dunggio, Abdul Saleh (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
Hypertension is the number one cause of death in the world and hypertension is the number three cause of death after stroke and tuberculosis namely 6.7 % of deaths of all ages in Indonesia. In many countries today, the prevalence of hypertension increases with lifestyle changes such as smoking, obesity, physical inactivity and psychosocial stress. Patients with hypertension at the Ambon Class IIA Penitentiary have experienced a significant and highest increase in 2018 with 39 people (44%). The purpose of this community service is to increase knowledge about hypertension through health education and lower blood pressure through hypertension gymnastics interventions. This method is by giving lectures and distributing leaflets about hypertension material to fostered citizens conducted on September 12, 2019 while for reducing blood pressure two exercise interventions are given, namely on September 20, 2019 and November 2, 2019. In addition this activity produces a Banner about Hypertension as information to the Guided Residents and the Video of Hypertension Gymnastics made by the Servants for use in Ambon Class IIA Prison. The results were obtained that there was an increase in knowledge after counseling, and there was a decrease in blood pressure for the inmates after participating in the Hypertension Gymnastics. The conclusion is Hypertension Exercise as an alternative to reduce pressure or be able to prevent and control the potential for stroke in hypertensive patients.